PENGUKURAN KONSERVATISME AKUNTANSI: SEBUAH LITERATUR REVIEW - Anggita Langgeng (Universitas PGRI Madiun, 2012)
This research is a study of the literature that discusses the measurement of accounting conservatism. Research about accounting conservatism raises several alternative methods that can be used to measure the level of accounting conservatism in a company. With reference to some previous literature it can be conclude that conservatism can be measured by several methods, including: 1) the market model of Basu (1997), 2) market to book ratio approach, 3) operating income approach, 4) the accrual of cash flow approach, 5) non-operating accrual approach.